Adaptive Governance Komunikasi Informasi Bencana Covid-19 Melalui Facebook dan Twitter oleh Pemerintah Provinsi Daerah Istimewa Yogyakarta - Rahmanto, Fajar; Zaenuri, Muchamad; Fauzi Rahmat, Al (Universitas Gadjah Mada, 2024)
The purpose of this study was to see the extent to which local governments have adapted to using social media to be handling with the Covid-19 disaster. This study uses a qualitative approach. Primary data collection by interview and secondary from social media accounts of local government organizations of the Special Province of Yogyakarta were analyzed with NVivo12 Plus. The results of this study the use of social media Facebook and Twitter by government agencies in the Special Region of Yogyakarta Province in handling covid to convey health information to the public. To facilitate access to accelerations of the spread of covid information from local governments externally by using social media and internally with the CMS (Corona Monitoring System). Finally, this study concludes that adaptive governance in the communication of pandemic disaster information using social media is an offer that can develop for local governments to adopt in the communication and disaster information management process. Adaptation of pandemic disaster management by utilizing social media can be a model for future efforts to build the adaptive capacity of local governments to be better prepared to deal with disasters that occur quickly.